Mystical Practices and Amulets: The Views of Abdul Karim Amrullah in Minangkabau Culture - Fauzan, Fauzan; Helfi, Helfi; Wadi, Fajrul; Daipon, Dahyul (Islam Transformatif : Journal of Islamic Studies, 2024)
This research aims to explore the conception of magic and amulets during the time of Abdul Karim Amrullah, both in terms of concept and practice in Minangkabau. Magic and amulets are distinct aspects but closely related in Minangkabau culture. In the past, shamans primarily controlled magic, while amulets, as countermeasures, were held by tarekat scholars. Over time, with the integration of custom and Islam in Minangkabau's philosophy "adat bersendi syara' and syara' bersendi kitabullah," there was a shift in expertise between magic and amulets. Both became skills possessed by both shamans and scholars. Subsequent developments showed a decline in magic practitioners, with some even becoming scholars. This research uses a qualitative descriptive approach. There are three main questions addressed in this article: first, how did magic and amulets emerge in Minangkabau; second, what is the depiction of the development of magic and amulets in Minangkabau; third, what is Abdul Karim Amrullah's conception of magic and amulets in Minangkabau. According to Abdul Karim Amrullah, magic, and amulets are practices that corrupt faith and can lead to polytheism. The proliferation of magic and amulets in the past was due to the rigid and fatalistic interpretation of "qudrah" by the Minangkabau society.